A facile strategy improving poly(vinyl chloride) stability by introducing unsaturated maleic acid-sorbitol ester and zinc maleic acid-sorbitol ester complex. (November 2020) - Wu, Jianyu; Tang, Zilun; Liu, Xiaochun; Lin, Wenjing; Feng, Minghui; Lin, Xiaofeng; Gu, Yuxin; Li, Yong; Yi, Guobin
Highlights: Unsaturated MS and Zn-MS with carbon double bonds can be used as multifunctional and efficient thermal stabilizers for PVC. MS and Zn-MS can endow PVC with various remarkable properties, including initial whiteness, long-term stability, lower-torque effect, less-implications for plate-out and higher transmittance. The addition of MS and Zn-MS could promote the dispersion of composition in the PVC matrix and improve the softness and toughness of the PVC chains. Abstract: Herein, as two types of rational designed thermal stabilizers, the maleic acid-sorbitol ester (MS) and zinc maleic acid-sorbitol ester complex (Zn-MS) with unsaturated carbon double bonds were synthesized to improve the initial whiteness and long-term thermal stability for polyvinyl chloride (PVC). The successfully synthesized MS and Zn-MS had three functions of replacing the labile chlorine on the PVC chains, reducing the "zinc burning" and absorbing the hydrogen chloride (HCl) released by PVC. After introducing the MS and Zn-MS, the stability time of PVC could be extended to more than 140 min and 120 min at 180 °C, respectively. Additionally, both the MS and Zn-MS had showed lower-torque effect on rheology and less-implications for plate-out in PVC. The addition of MS and Zn-MS could promote the dispersion of composition in the PVC matrix and endow the PVC with better strength and toughness. Meanwhile, in contrast with ZnSt2 or CaSt2, the transparency of PVC sheet stabilized by MS and Zn-MS also showed the higher transmittance, which severally reached to 57.2% and 72.1%.